How do people explore a large concourse in university campus? A computational analysis. Issue 4 (27th December 2018) - Kim, Youngchul; Kim, Tae Wan
Graphical abstract: Abstract: Large concourses have been developed in shopping malls, bus and train terminals, concert, theatre halls, and other places where people stand or/and are in constant motion. This study aims to develop a novel method to analyze people's space use and navigation, demonstrate how people explore a large space, specifically a concourse in a university, and determine relationships of space with people's movements and activities. By collecting empirical data of spatial uses in a large concourse and implementing a method of spatial analysis based on spatial grids to analyze such data, this study seeks to verify how effectively people's movements and activities can be established in a large space and which features have significant effect in developing and managing a large space. A total of 865 activities in 265 days were collected and analyzed in a large space of a concourse in a university campus. By adopting a locational-based method of geographical analysis, the proposed method effectively illustrated relationships of people's movement, activities, and satisfaction in visual and quantitative values. As a result, spatial features were found to be significant elements in improving spatial satisfaction. Space environment performance, spatial form, user capacity, equipment adequacy, and equipment conditions were major spatial features considered for improving people's satisfaction in a large space.